1978
DOI: 10.1007/bf00224365
|View full text |Cite
|
Sign up to set email alerts
|

Relaxin, a male hormone?

Abstract: Convincingly demonstrated by immunocytological methods in females of several mammalian species, relaxin has not yet been localized in the male. Immunocytologically, a related antigen was identified in adult normal boar testes using and anti- [NIH P-relaxin/HSA] antiserum free of anti HSA Abs. A strong reaction was observed in interstitial cells, a weaker but very clear one in Sertoli cells. NIH P-relaxin and HC1-acetone extracts of either corpora lutea from pregnant sows or boar testes inhibited the immunofluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0

Year Published

1979
1979
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 4 publications
2
7
0
Order By: Relevance
“…The intense immunoreactivity of relaxin within the testicular interstitium (Leydig cells) was consistent with previous reports in boars employing the immunological approach [ 23 , 43 , 24 ]. Kato et al, used up to 10 month old pigs to detect relaxin protein signals that were restricted to the Leydig cells [ 24 ], and therefore confirmed a pioneer study that reported weaker relaxin signals in boar Sertoli cells [ 43 ].…”
Section: Discussionsupporting
confidence: 92%
“…The intense immunoreactivity of relaxin within the testicular interstitium (Leydig cells) was consistent with previous reports in boars employing the immunological approach [ 23 , 43 , 24 ]. Kato et al, used up to 10 month old pigs to detect relaxin protein signals that were restricted to the Leydig cells [ 24 ], and therefore confirmed a pioneer study that reported weaker relaxin signals in boar Sertoli cells [ 43 ].…”
Section: Discussionsupporting
confidence: 92%
“…Cameron et al ( 1982) used the same antigen to absorb their antiserum before control stainings when they reported the occurrence of relaxin in the armadillo prostate gland. Dubois & Dacheux (1978), using antiserum prepared against crude porcine relaxin (NIH porcine relaxin, 442 U/mg) coupled to human albumin, detected relaxin-like immunoreactivity in the testis of the adult boar. However, Arakaki et ai (1980) were unable to repeat this work with an antiserum raised against highly purified relaxin, and our negative results on the human testis are consistent with this.…”
Section: Discussionmentioning
confidence: 99%
“…Relaxin has been identified by an immunoperoxidase method in the armadillo prostate gland (Cameron, Cortón & Larkin, 1982). In the boar, relaxin was first reported to be present in the testis (Dubois & Dacheux, 1978), but when antiserum against highly purified relaxin was used, specific fluorescence was not observed (Arakaki, Kleifeld & Bryant-Greenwood, 1980). The purpose of the present study was to determine the tissue origin of relaxin in men.…”
Section: Introductionmentioning
confidence: 94%
“…An earlier study indicated the presence of immunoreactive RLN in the interstitial cells and Sertoli cells of the boar testis by indirect immunofluorescence with antiserum for crude porcine RLN (Dubois & Dacheux 1978), although subsequent studies could not confirm this finding when repeated with antiserum for purified porcine RLN (Arakaki et al 1980, Kohsaka et al 1992). Nevertheless, a study using the reverse transcription and PCR (RT-PCR) method demonstrated the presence of RLN transcripts in the testis (Lobb et al 1995).…”
Section: Introductionmentioning
confidence: 93%